Enhancement of nitrogen fixation rates by unicellular diazotrophs vs. Trichodesmium after a dust deposition event in the Canary Islands. (14th December 2012) - Benavides, Mar; Arístegui, Javier; Agawin, Nona S. R.; Cancio, José López; Hernàndez-León, Santiago
Abstract : We studied the relationship between atmospheric dust deposition, N2 fixation rates, and the abundance of unicellular diazotrophs and Trichodesmium in weekly or biweekly samplings over 3 months in the Canary Islands. On average, N2 fixation rates by unicellular diazotrophs and Trichodesmium were low (0.2 nmol N L −1 h −1 and 1.66 × 10 −3 nmol N L −1 h −1, respectively). However, N2 fixation rates associated with unicellular diazotrophs increased by 86% and 92% after a peak of aerosol concentration in samples incubated in both light and dark, while the rates associated with Trichodesmium diminished by 34% and 92% in the light and in the dark, respectively. The abundance of unicellular diazotrophs ranged from 4 cells L −1 to 54 cells L −1 . After the input of aerosols, 66% of the unicellular diazotrophs observed were attached to putatively organic matter particles. Trichodesmium abundance was low (average of 0.5 trichomes L −1 ), mainly in the form of free trichomes, which might hinder the ability of these organisms to take advantage of the Fe dissolved in the water column after dust deposition events. We also highlight the importance of monitoring short‐term variability of N2 fixation in order to have a better understanding of the nitrogen cycle in the ocean.